Construction and Comparation of Critical Nitrogen Concentration Dilution Curves for Spring and Autumn Potato in China - Jiacheng Bai; Yuheng Liu; Yixi Chen; Siyu Wang; Zhi Zhang; Ximing Xu; Xing Shu; Xu Zhao; Yueming Zhu; Zhihao Qiu; Guoquan Lu; Zunfu Lv (Agronomy)
Nitrogen is one of the essential nutrients for the growth and development of potato plants. The precise application of nitrogen can improve the yield and quality of potatoes and enhance their resistance to diseases. The changes in the critical N dilution curves of the shoot, root, and whole plants of potato were analyzed according to different N levels. The difference in the critical nitrogen concentration dilution curve of potatoes in spring and autumn was discussed. It is of great significance for the precise management of nitrogen fertilizer in spring and autumn potatoes. In this experiment, four field experiments were conducted using two potato cultivars (Zheshu956 and Yongma1) with four varying N application levels (N0–N3). Two identical varieties were planted at the same location in the spring and autumn and there was no significant difference in the selection of the same varieties between the two seasons. The dry matter and nitrogen concentration of roots, stems, leaves, and tubers were measured after transplantation at different stages. The results showed that the critical nitrogen concentration models for the shoot, root, and whole plant of potatoes were constructed as follows: spring potato shoot, N = 4.8712 W−0.203, root, Nc = 1.8477 W−0.157, and whole plant, Nc = 4.1679 W−0.293; autumn potato shoot, Nc = 3.8653 W−0.204, root, Nc = 2.1529 W−0.158; and whole plant, Nc = 3.2569 W−0.304. The critical nitrogen curves for the aboveground part and the whole plant of spring potato were significantly higher than that of autumn potato. Under N2 (160 kg ha−1) treatment, both spring and autumn potatoes reach their maximum yield. The critical nitrogen concentration dilution curve based on the whole plant was determined to be more appropriate for potatoes. The critical nitrogen concentration curves of potatoes in spring and autumn were significantly different for the aboveground part and the whole plant, but there was no significant difference for the underground part. The separately constructed nitrogen nutrition indices can be used to diagnose the nitrogen requirements of spring and autumn potatoes.